DOUBLE TRACK SYSTEM IN CRIMINAL SANCTION AGAINST NARCOTICS ABUSE - Mujito, Mujito; Darmawan, Prof. Dr. Arif; Yudianto, Dr. Otto; Mangesti, Dr. Yovita Arie (jfpublisher, 2022)
The development of era shows a strong tendency to change the perception of narcotics addicts whom facing imprisonment and rehabilitation. The punitive approach may hide people who need a treatment, and the narcotic addicts may have fear arrest when they show up. Therefore, this situation prevents addicts from participating in treatment and rehabilitation programs. The output of the research is the essence of Double Track System m for narcotics abuse to create equality in the imposition of criminal sanctions and action sanctions against narcotics abuse. The narcotics abusers, addicts and it victims that violate the criminal law, they are required to get rehabilitation as a form of recovery effort (curative) and make the abuser aware that his actions are detrimental to himself and his future. The efforts to overcome narcotics abuse through the Double Track System sanction have the characteristics of exploring the benefits of law to prevent criminal acts, especially the narcotics abusers, then the main target is to utilize the model of action sanctions and criminal sanctions in proportional concept as a solution to provide the effectiveness in eradicating deviant narcotic use massively and comprehensively.